Write Back Soon: Mass Incarceration and “Writing Intensive” Vulnerability - Owen, Ianna Hawkins (Radical Teacher, 2019)
This is a reflection about teaching first year undergrads at an elite private institution in a predominantly white rural area about blackness and the prison industrial complex in a “writing intensive” course through the use of open letters and the politicization of vulnerability.